2008
DOI: 10.1093/ndt/gfn471
|View full text |Cite
|
Sign up to set email alerts
|

Renal dysfunction in acute stroke: an independent predictor of long-term all combined vascular events and overall mortality

Abstract: Renal function on admission appears to be a significant independent prognostic factor for long term mortality and new cardiovascular morbidity over a 10-year period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
143
3
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(165 citation statements)
references
References 31 publications
17
143
3
2
Order By: Relevance
“…Similar results were found by Hoshino and colleagues 19 in their study among stroke patients with mild to moderate renal dysfunction. Tsagalis et al, 20 observed a similar rates (28%) of renal dysfunction in acute stroke patients suggesting a significant prevalence of CKD in stroke sufferers .…”
mentioning
confidence: 78%
“…Similar results were found by Hoshino and colleagues 19 in their study among stroke patients with mild to moderate renal dysfunction. Tsagalis et al, 20 observed a similar rates (28%) of renal dysfunction in acute stroke patients suggesting a significant prevalence of CKD in stroke sufferers .…”
mentioning
confidence: 78%
“…46 This study showed that although estimated GFR was associated with increased risk, the risk was lower than that observed for cystatin C. 46 Possible reasons for the stronger association between serum cystatin C and mortality compared to creatinine and estimated GFR are not completely clear, but are likely due, at least in part, to non-GFR determinants of serum cystatin C. 47 In previous studies, it was documented that renal dysfunction is independent predictor of short-and long-term mortality in patients with stroke. [9][10][11][12][13][14] In most studies, creatinine or estimated GFR based on creatinine were used to define renal dysfunction. The predictive value of cystatin C has not been fully established in patients suffering from ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] In several studies, higher prevalence of renal dysfunction in patients with ischemic stroke was reported. 9,10 Furthermore, renal dysfunction was also an independent predictor of mortality in patients with stroke. 9,[11][12][13] Patients with renal dysfunction are also at greater risk of future ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly, one-third of acute stroke patients have renal dysfunction. 18 In this study, CKD was found 26.9% in acute ischemic stroke patients.…”
Section: Discussionmentioning
confidence: 49%